Kedudukan Perceraian Karena Peralihan Agama (Murtad) Dalam Perspektif Hukum Islam Dan Undang-Undang Perkawinan - Aziza, Mutia Sakiyah; Hanifah, Mardalena; Darnia, Meriza Elpha (Universitas Pahlawan Tuanku Tambusai, 2024)
Divorce is the termination of a marriage by order of a judge or what is known as a demand by one of the parties during the marriage. The Marriage Law does not regulate divorce due to conversion, but in Article 116 letter (h) of the Compilation of Islamic Law, apostasy is stated as one of the reasons for divorce, while Islamic law states that if one of the parties apostatizes, the marriage is void. This has caused confusion among the public about how to deal with the problem of marriages that end due to conversion/apostasy. The purpose of this study is to review the legal position of divorce due to conversion (apostasy) in Islamic law and the Marriage Law and the considerations of the panel of judges in deciding divorce cases number 686/Pdt.G/2022/PA.Tgrs and number 104/Pdt.G/2022/PA.Pkc due to conversion (apostasy). This research is a normative legal research using the comparative law method. From the results of this research, it can be concluded that the legal status of a marriage is if one of the husband or wife changes religion or apostates according to Islamic law, the marriage becomes fasakh (void), and if one of the husband and wife leaves Islam or apostates and the apostasy is not or has not been submitted to the court, and the court has not yet decided, then their marriage is still considered valid and valid.